Dairy intake in relation to breast and pubertal development in Chilean girls - Gaskins, Audrey J; Pereira, Ana; Quintiliano, Daiana; Shepherd, John A; Uauy, Ricardo; Corvalán, Camila; Michels, Karin B (The American journal of clinical nutrition, 2017)
Frequent dairy consumption in childhood has been related to higher growth-hormone concentrations that may affect mammary gland and pubertal development. We evaluated the relation of dairy intake to breast composition at Tanner stage 4 and age at menarche. A total of 515 Chilean girls are included in the Growth and Obesity Cohort Study. The subjects have been followed longitudinally since they were 3-4 y old (from 2006 to the present). Starting in 2013, diet was assessed every 6 mo via a 24-h recall. The breast fibroglandular volume (FGV) was measured with the use of dual-energy X-ray absorptiometry at Tanner stage 4. The date of menarche was reported every 6 mo. Our analysis included 290 girls with data on prospective diet and breast composition and 324 girls with data on prospective diet and age at menarche. The mean ± SD breast FGV and percentage of fibroglandular volume (%FGV) (i.e., FGV divided by total breast volume times 100) at Tanner stage 4 was 81.7 ± 32.2 cm and 42.0% ± 16.7%, respectively. Only sweetened, artificially flavored milk-based drinks were associated with the %FGV with girls who consumed >125 g/d having a %FGV that was 4.5% (95% CI: 0.9%, 8.1%) higher than that of girls who consumed none ( -trend = 0.007). Yogurt intake was associated with a lower FGV. Specifically, girls who consumed >125 g yogurt/d had -10.2 cm (95% CI: -20.2, -0.3 cm ) less FGV than did girls who consumed no yogurt ( -trend = 0.03). The majority (90.7%) of girls in our cohort attained menarche before the data analyses with a mean ± SD age at menarche of 11.9 ± 0.7 y. In multivariable models, low-fat dairy, low-fat milk, and yogurt intakes were associated with a later age at menarche. In particular, girls who consumed >125 g yogurt/d had menarche, on average, 4.6 mo (95% CI: 1.9, 7.4 mo) later than girls who consumed no yogurt ( -trend = 0.01). More-frequent consumption of sweetened, artificially-flavored milk-based drinks is associated with a higher %FGV, whereas higher yogurt intake is associated with a lower FGV and delayed age at menarche in Chilean girls.